Group versus Individual Prenatal Care and Maternal Outcomes in Jordan: An Integrative Review - Etap Swaiti (Jordan University of Science and Technology, 2023)
Background: There has been an increasing trend on the implementation of group prenatal care where women go along as a group rather than as individuals to attend their prenatal appointments. However, there is a paucity of studies that compared group versus traditional individual prenatal care within Jordanian healthcare settings. Aim:  To examine the differences between traditional individual and group prenatal care based on maternal outcomes among Jordanian pregnant women Methods: An integrative review of studies published between 1993 and 2023 was performed across three databases (CINAHL, Medline and PubMed). No studies were found that investigated group prenatal care and no studies were found that examined maternal outcomes relating to group prenatal care. Nevertheless, a total of 9 studies were found that examined outcomes relating to traditional prenatal care. Results: Three themes were identified in relation to traditional prenatal care for Jordanian women namely (1) limitations of prenatal care, (2) barriers to prenatal care, and (3) expectations of pregnant women. However, even data on the relationship between traditional prenatal care and maternal outcomes were scarce such that where there was evidence of prenatal care, the quality and extent of data were inadequate to strongly infer on the effectiveness of traditional prenatal care programs for pregnant Jordanian women. Conclusion: There is a significant gap in literature on the implementation of group prenatal care among pregnant Jordanian women. Future research can investigate how developing, integrating and implementing group prenatal care for pregnant Jordanian women can influence maternal and neonatal health outcomes.